The Motif of 76KRKCSK in Bm65 Is an Efficient Nuclear Localization Signal Involved in Production of Infectious Virions - Li, Guohui; Qi, Xinyu; Chen, Huiqing; Hu, Zhaoyang; Chen, Fangying; Deng, Liang; Guo, Zhongjian; Chen, Keping; Tang, Qi (Frontiers in Microbiology, 2019)
orf65 (Bm65) of Bombyx mori nucleopolyhedrovirus (BmNPV) codes for a putative 104-amino-acid protein containing three cysteine residues with a putative molecular mass of 12.2 kDa. Previous study showed that Bm65 is accumulated mainly in the nucleus and involved in the repair of UV-damaged DNA. However, the mechanism of nuclear import of Bm65 remains unclear. In this study, a SDS-stable Bm65 tetramer was found in virus-infected BmN cells, and alanine substitutions for the three cysteine residues did not affect the formation of Bm65 tetramer. Additionally, various clusters of basic amino acid of the BmNPV orf65 (Bm65) protein were identified as efficient nuclear localization signals (NLS). Firstly, transient expression of GFP-fused truncated Bm65 variants revealed that the 76KRKCSK motif functions as the NLS. This was also confirmed by alanine substitution in the 76KRKCSK motif, which caused attenuated nuclear localization of Bm65. Next, the 76KRKCSK motif-mutated bacmid was generated and the 76KRKCSK motif was also found to be important for nuclear localization of Bm65 in virus-infected condition. Lastly, analyses of Flag-tagged Bm65 expressing bacmids revealed that the mutation in 76KRKCSK motif did not affect the synthesis of tetrameric form of Bm65 but severely impaired production levels of infectious virion. In conclusion, Bm65 exists in mainly a tetrameric form in virus-infected cells, which may be involved with production levels of infectious virions.